The value of 7 peripheral blood serum ratios in diagnosis and prediction of disease activity of patients within inflammatory bowel disease individuals - Pan, Jun; Li, Jiao; Gao, Yuanjun (Frontiers in Medicine, 2023)
Objective: In recent years, a number of studies have suggested that inflammation-based biomarkers can be applied in the diagnostics and prognostic testing of disease. However, the association between these ratios and inflammatory bowel disease (IBD) remains unclear. We aimed to investigate the role of these inflammation-based ratios in patients with IBD. Methods: Retrospective analysis of 362 patients with IBD and 100 healthy individuals from January 2016 and December 2021. The receiver operating characteristic curve and logistic regression analysis was applied to explore the diagnostic and predictive performance of the seven ratio markers [neutrophil- to-albumin ratio (NAR), neutrophil-to-pre-albumin ratio (NPAR), albumin-to-alkaline-phosphatase ratio (AAPR), albumin-to-globulin ratio (AGR), albumin-to-fibrinogen ratio (AFR), fibrinogen-to-pre-albumin ratio (FPR), and Prognostic Nutritional Index (PNI)] regarding to disease activity in IBD individuals. Results: Compared with healthy controls, patients with Crohn’s disease (CD) or ulcerative colitis (UC) exhibited higher levels of NAR, NPAR, FPR (P<0.001), lower levels of AAPR, and PNI (P<0.001). Multivariate logistic regression showed that the level of NPAR (OR=1.12, 95%CI: 1.02–1.23, P=0.016) and AGR (OR=1.01, 95%CI: 1.01–1.12, P<0.001) was an independent risk factor of IBD. Then, we found the level of NPAR (OR=1.10, 95%CI: 1.01–1.20, P=0.02) and PNI (OR=0.83, 95%CI: 0.71–0.96, P=0.01) was independently associated with disease activity. Besides, a positive association was observed between the level of NPAR and two clinical scores [Harvey Bradshaw index (HBI) in patients with CD, Mayo score in patients with UC]. Finally, the level of NPAR (P=0.002) and PNI (P=0.003) showed a significant difference in the IBD-associated neoplasia group and IBD without neoplasia group. Conclusions: Our data first suggests NPAR as a putative biomarker for diagnosing and predicting disease activity in patients with IBD. Investigations involving a larger number of IBD individuals are necessary to validate its use as an easily obtained peripheral blood biomarker of IBD.